Chemical constituents of the fruits from Fissistigma oldhamii (Hemsl.) Merr. growing in Vietnam - Dung, Vo Cong; Quynh Giang, Nguyen Thi; Thang, Tran Dinh; Hoang, Vu Dinh (Vietnam Journal of Chemistry, 2016)
Phytochemical studied on methanol extract of fruits Fissistigma oldhami (Hemsl.) Merr.  (Annonaceae) led to the isolation of four flavonoids: 6-hydroxy-5,7,8-trimethoxy flavanone, 2’,5’-dihydroxy-3’,4’,6’-trimethoxy chalcone, quercetin, rutin and two steroids: b-sitosterol (5) and b-sitosterol-3-O-b-D-glucopyranoside (6). The structures of the compounds were established on the basic of spectroscopic methods (UV, IR, MS, 1D-NMR and 2D-NMR) and comparison with literature data. This is first time the 6 compounds isolated from the plant. Keywords. Fisistigma oldhamii, Annanoceae, flavonoids, steroids.